The effect of partially fix in least square / Mohamad Amirul Rozali - Rozali, Mohamad Amirul (2021)
The Department of Survey and Mapping Malaysia (DSMM) having an issues regarding adjustment especially related to least square adjustment (LSA). The way of adjusting the data using LSA are still can be improved by DSMM. Hence, the aim of this research is to study is to investigate the impact of partially fix in cadastral adjustment. To achieve this aim, the objectives of this study identify the impact weight to the observation precision and to investigate the impact of partially fix to the adjusted coordinate. Thus, most suitable adjustment method is obtained according to the results of the application.